Transcripts of the Drosophila blastoderm-specific locus, terminus, are concentrated posteriorly and encode a potential DNA-binding finger. - Baldarelli, R.M.; Mahoney, P.A.; Salas, F.; Gustavson, E.; Boyer, P.D.; Chang, M.F.; Roark, M.; Lengyel, J.A. (Developmental Biology, 1988)
The commitment of cells to specific fates, as well as the transitions in the cell cycle and transcription that occur at the cellular blastoderm stage of Drosophila embryogenesis, suggest that there are genes with unique functions expressed specifically at this stage. In an attempt to identify such genes, we used molecular screening to isolate several loci which encode blastoderm-specific transcripts (Roark et al., (1985). Dev. Biol. 109, 476-488). We report here the complete nucleotide sequence of one of these genes, terminus (ter), which maps to 75C1,2. The predicted ter protein possesses a transcription factor IIIA (TFIIIA)-like putative Zn-binding, DNA-binding finger. The ter RNA, detected by in situ hybridization, is distributed uniformly in the embryo during the syncytial blastoderm stage, and then becomes more concentrated in the posterior during the late cellular blastoderm stage. During gastrulation, the RNA is most concentrated in the amnioproctodeal invagination; it is also found at a lower concentration in the ventral furrow and in the anterodorsal neurogenic region. By the end of germ band extension, ter RNA is no longer detected.